Nomenclatural novelties in Petrosedum (Crassulaceae) - Gallo, Lorenzo (Phytotaxa, 2017)
The recent paper of Nikulin et al. (2016), states the needs to move the Sedum ser. Rupestria Berger (1930: 456) to the genus Petrosedum Grulich (1984: 39); most of the recombinations are already in hand but some still remain to carried out and some names are illegitimate. In order to achieve this goal, a new name and a new combination under Petrosedum for two French hybrid taxa are proposed here.